Sustainable coexistence of the parental species and hemiclonal interspecific hybrids is provided by the variety of ontogenetic strategies - Shabanov, D.; Usova, O.; Kravchenko, M.; Biriuk, O.; Leonov, A.; Korshunov, O.; Mair, Quentin; Meleshko, O.; Newman, Ju.; Vladymyrova, M.; Zholtkevych, G. (Herpetological Facts Journal, 2015)
Factors determining the sustainability of Hemiclonal Population Systems in which the interspecies hybrids Pelophylax esculentus complex coexist with members of parental species were studied using a combination of empirical data and computer simulation modeling. The empirical data demonstrates the existence of different intrapopulation strategies by partitioning a sample of individuals into two groups on the basis of their body size at a given age and comparing selected groups in terms of factors such as growth rate, life span, females’ fecundity and the age at which breeding commences. Then by using simulation modeling, we study the probable importance of intrapopulation ontogenetic strategies for the stability of Pelophylax esculentus complex HPS.
Keywords: Pelophylax esculentus complex; skeletochronology; strategy; undersize; oversize; simulation; hemiclonal population systems